Tumor Mammae Aberrans Dextra pada Wanita Usia 16 Tahun - Maghfiroh Rahma Rafie; Adi Rizka (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Mammae aberrans in the axilla is a developmental abnormality caused by the persistence of breast tissue along the milk line and can cause fluctuating axillary masses due to hormonal stimulation, with a reported prevalence of approximately 0.4–6%. Methods: This article is presented as a descriptive case report based on data from the Department of Surgery at Cut Meutia Regional General Hospital, North Aceh, including medical history, physical examination, routine blood tests, fine needle aspiration biopsy (FNAB), excision, histopathological examination, and follow-up. Results: A 16-year-old female patient complained of a lump in her right axilla for approximately two years, which had enlarged in the last month and caused severe pain before menstruation. Examination revealed a mass measuring approximately 3×3×2 cm, without lymph node enlargement, and normal routine blood tests. Two FNAB punctures showed fat droplets/matrix without epithelial proliferation or malignant cells (benign smear) with the impression of aberrant mammary glands. The patient underwent mass excision; histopathology showed mature fatty tissue and fibrocollagen accompanied by ductular proliferation without signs of malignancy, and at the 1-week follow-up, the pain had disappeared and the lump was no longer visible. Discussion: The cyclic pain pattern associated with menstruation is an important clue for distinguishing aberrant mammary glands from differential diagnoses of axillary masses in adolescents, while excision provides diagnostic certainty and symptom improvement. Conclusion: Mammae aberrans should be considered in adolescents with axillary masses affected by the menstrual cycle, and excision is recommended in symptomatic cases for histopathological confirmation and resolution of complaints.